2017
DOI: 10.9740/mhc.2017.09.181
|View full text |Cite
|
Sign up to set email alerts
|

Student pharmacists' social distancing toward people with mental illness

Abstract: Results indicate social distancing is prominent among pharmacy students. Results may be used in the future to help identify solutions for improving social distancing and increasing pharmacy student interaction to patients with mental illness. Further training related to mental illness may assist with decreasing social distancing among pharmacy students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“… 31 Data from high-income countries suggests that stigma as measured by social distancing is prominent in pharmacy students. 32 Stigmatising attitudes toward mental illness in healthcare professionals and healthcare students were found to be high in our sample, albeit to a lesser degree than the general public. Studies from low- and middle-income countries have described stigmatising attitudes of health professionals toward mental illness, and it is possible that health education reduces negative perceptions but does not eliminate stigma altogether.…”
Section: Discussionmentioning
confidence: 48%
“… 31 Data from high-income countries suggests that stigma as measured by social distancing is prominent in pharmacy students. 32 Stigmatising attitudes toward mental illness in healthcare professionals and healthcare students were found to be high in our sample, albeit to a lesser degree than the general public. Studies from low- and middle-income countries have described stigmatising attitudes of health professionals toward mental illness, and it is possible that health education reduces negative perceptions but does not eliminate stigma altogether.…”
Section: Discussionmentioning
confidence: 48%
“…Pandemics and preventive social distancing have been studied from a medical perspective regarding disease containment (Reluga, 2010; Valdez et al , 2012; Adolph et al , 2021; Sharma et al , 2020; Wilder-Smith and Freedman, 2020), but few studies have focused on ethnic or racial social distancing (Yogeeswaran and Dasgupta, 2014; Ramasubramanian et al , 2017) and social distancing concerning mental illness (Seaton and Piel, 2017; Lundquist and Gurung, 2019), and even less have looked at social distancing and human PI.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that pharmacy students demonstrate stigma and negative attitudes toward these patients, including increased social distance (decreased willingness to engage in various social interactions) and misconceptions. [8][9][10][11] Because stigma can negatively impact patient care, it is important to consider methods of decreasing stigma during pharmacy school. Although traditional didactic education has not reduced stigma in pharmacy students, 9,12 lower social distance and increased positive attitudes have been seen in students who had previously been employed in a pharmacy, had personal experience with mental illness, or were members of a mental health-focused college organization.…”
Section: Introductionmentioning
confidence: 99%